A Study on the Teaching of Vocabulary through Popular English Songs: A Pre-Experimental Study To The Eighth Grade Students of SMP Negeri 6 Sengah Temila In The Academic Year 2013/2014 - Mosniati, Mosniati (IKIP-PGRI Pontianak, 2014)
This research was to find out the effectiveness of popular English songs and to find out the significance of the effectiveness of popular English songs in teaching vocabulary to the eighth grade students of SMP Negeri 6 Sengah Temila in the academic year 2013/2014. The research design was pre-experimental design. The researcher chose the eighth grade students of SMP Negeri 6 Sengah Temila as the participant who had been involved in this research. Particularly, the VIII B was considered as a sample of this research. Furthermore, based on the findings, it was found that teaching vocabulary through popular English songs was effective. The effectiveness of popular English songs was analyzed by effect size formula, thus, it was categorized as medium influence. Meanwhile, the result of Wilcoxon signed rank indicated that Z score was smaller than df score, it meant the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. The study concluded that the use of popular English songs should be effective to be applied in teaching and learning process especially in teaching vocabulary.